USER IMMERSION CONTROL: THE CASE OF A PSYCHOLOGICAL TESTING SYSTEM WITH FEEDBACK - A.V. Ivaschenko; M.V. Aleksandrova (Модели, системы, сети в экономике, технике, природе и обществе, 2024)
Background. The paper discusses a challenging problem of increasing the reliability of automated psychological testing by controlling the depth of user immersion in the immersive reality environment. Materials and methods. Based on a previously introduced model of an immersive environment, the article proposes algorithms for managing the user’s involvement in such an environment, allowing enhancing the depth of immersion and maintaining the user’s attention under the influence of external and internal distractions. It is proposed to consider the indicator of instability (distraction) of attention as the main parameter characterizing the depth of user immersion. To attract and maintain the user’s attention to the objects related to the target topic, taking into account the presence of a large number of distracting objects in immersive reality, it is proposed to introduce additional objects that are most relevant to the user’s current interest, as well as to select an adequate frequency of their appearance. Results. The proposed algorithms were implemented and studied in psychodiagnostics within the framework of a psychological testing software package to build an additional feedback loop. For this purpose, the system includes a computer vision subsystem, including a video camera, oculography (eye-tracking) tools and software for video monitoring of the patient’s motor activity. The software tracks the total volume of facial expressions, head and eye movements, and also identifies the current emotional state using an artificial neural network. To ensure high user involvement, personalization of the user interface and tests is provided. Conclusions. The developed hardware and software complex for psychological diagnostics and medical rehabilitation allows, unlike analogues, to implement feedback on monitoring and control of patient involvement.